Pengaruh Penerapan Green Accounting dan Penerapan Corporate Social Responsibility (CSR) terhadap Pertumbuhan Harga Saham: (Studi Perusahaan Manufaktur di Sektor Industri Dasar dan Kimia) (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study analyzes the effect of green accounting and Corporate Social Responsibility (CSR) disclosure on stock price growth in manufacturing companies in the basic and chemical industries listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The study adopts a quantitative approach using secondary data, including annual reports and stock prices, with a sample of 67 observations selected through purposive sampling. Multiple linear regression is employed to test the proposed hypotheses. The findings indicate that the implementation of green accounting does not significantly affect stock price growth, suggesting that environmental accounting practices may not yet be a key determinant for investors. In contrast, CSR disclosure has a significant but negative impact on stock price growth. Despite the positive intentions behind CSR initiatives, investor responses remain cautious, reflecting the challenges of rewarding long-term social and environmental commitments in the short term. This result suggests that while CSR activities are beneficial in promoting corporate sustainability, their impact on stock prices may take longer to materialize. However, the study also highlights that effective green accounting and transparent CSR disclosure can increase stakeholder trust and potentially drive sustainable stock price growth over time. The research contributes to the accounting literature by providing insights into the interaction between environmental accounting practices, social responsibility, and market performance. Furthermore, it offers practical applications for corporate management, investors, regulators, and the general public to understand how these factors influence financial performance and long-term sustainability